Intra-regional diversification of the level of entrepreneurship relative to the competitiveness of eastern Poland poviats - Dziekański, Paweł; Lipa, Adrian (Wewnątrzregionalne zróżnicowanie poziomu przedsiębiorczości względem konkurencyjności powiatów Polski Wschodniej, 2020)
The process of a unit’s operation takes place in a space of endogenous and exogenous resources. Entrepreneurship plays an important role in the efficient allocation of resources. The purpose of the article is to analyse the diversity of the level of entrepreneurship of counties (‘powiat’) in relation to their competitiveness using the synthetic measure of counties of eastern Poland. Data from BDL CSO for 2010-2017 were used as source material. Entrepreneurship and competitiveness are the main determinants of the region’s development. A much higher level of competitiveness was characteristic of counties with a higher level of entrepreneurship measure, and the best units are: Mielec, Bieszczady, Leski, Tarnobrzeg, Mielec and Białystok. In 2010, the entrepreneurship measure ranged from 0.04 to 0.43, in 2017 from 0.13 to 0.53 (competitiveness measure from 0.31 to 0.46; from 0.32 to 0.52). The position of counties was shaped by investment outlays, gross value of fixed assets, sold production of industry, economic entities, and own income
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2020; vol. 64, nr 1, s. 30-43
Keywords: entrepreneurship; competitiveness; synthetic measure; country; eastern Poland; przedsiębiorczość; konkurencyjność; miara syntetyczna; powiat; Polska Wschodnia